1996
DOI: 10.1038/384353a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myocardial endothelin pathway improves long-term survival in heart failure

Abstract: Occlusion of the diseased coronary artery in humans causes acute myocardial infarction, survivors of which have a high risk for the development of chronic heart failure. Cardiac myocytes and vascular endothelial cells produce endothelin-1 (refs 2-4), which increases the contractility of cardiac muscle and of vascular smooth muscle cells. Endothelin-1 also exerts long-term effects such as myocardial hypertrophy, and causes cellular injury in cardiac myocytes. Production of endothelin-1 is markedly increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
316
3
9

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 588 publications
(339 citation statements)
references
References 20 publications
11
316
3
9
Order By: Relevance
“…24,25 There are several studies showing beneficial effects of the ET receptor blockade on survival, hemodynamic parameters, and histological remodeling. [11][12][13] This study has demonstrated for the first time that long-term treatment with an ET A receptor antagonist prevents electrical remodeling such as reduction of I to , I K , and I Ca,L and prolongation of APD in ventricular cells and improves QT prolongation in the ECG of cardiomyopathic hamsters. Beneficial effects of the ET A antagonist TA-0201 on survival rate might be partly ascribed to the inhibition of ventricular arrhythmias by lessening electrical inhomogeneity resulting from downregulation of ion channels.…”
Section: Matsumoto Et Al Et a Receptor Blockade On Electrical Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 There are several studies showing beneficial effects of the ET receptor blockade on survival, hemodynamic parameters, and histological remodeling. [11][12][13] This study has demonstrated for the first time that long-term treatment with an ET A receptor antagonist prevents electrical remodeling such as reduction of I to , I K , and I Ca,L and prolongation of APD in ventricular cells and improves QT prolongation in the ECG of cardiomyopathic hamsters. Beneficial effects of the ET A antagonist TA-0201 on survival rate might be partly ascribed to the inhibition of ventricular arrhythmias by lessening electrical inhomogeneity resulting from downregulation of ion channels.…”
Section: Matsumoto Et Al Et a Receptor Blockade On Electrical Remodelingmentioning
confidence: 99%
“…9 -11 It has been reported that long-term blockade of the endothelin-A (ET A ) receptor ameliorates ventricular contractile dysfunction in various animal models of congestive heart failure. 12,13 More recently it has been found that long-term treatment with TA-0201, a selective ET A antagonist, 14 improved cardiac function and survival rate in cardiomyopathic Syrian hamsters. 11 Since the BIO 14.6 cardiomyopathic hamsters were reported to have ventricular arrhythmias in the late stage, 15 the ET A receptor antagonist might prevent sudden cardiac death by inhibiting electrophysiological alterations associated with cardiomyopathic contractile dysfunction.…”
mentioning
confidence: 99%
“…ET-1 is the main isoform released from the endothelium and acts in a paracrine or autocrine fashion by interacting with ET receptors in vascular smooth muscle (VSM) and endothelial cells, and thereby modifying vascular function and cell growth and proliferation [10]. ET-1 is also produced by airway epithelial cells, macrophages, fibroblasts, cardiomyocytes and neurons [9,[11][12][13]. ET-2 is expressed by intestinal epithelial cells, while ET-3 is produced by intestinal epithelial cells, brain neurons and renal tubular epithelial cells [9,14].…”
Section: Et Synthesismentioning
confidence: 99%
“…We used the left coronary artery-ligated rat model of CHF, which is well established (24,(26)(27)(28). To produce rats with CHF, left ventricular free wall myocardial infarction was induced in 7-wk-old male rats (CHF group) according to the method described in our previous papers (26)(27)(28).…”
Section: Animals and Protocolmentioning
confidence: 99%